A diffuse-interface compact difference method for compressible multimaterial elastic–plastic flows. (15th February 2022) - Li, Xiang; Ma, Dong-Jun; Liu, Nan-Sheng; Wang, Pei
Abstract: In this paper, a novel high-order numerical method is proposed for the simulation of compressible multimaterial solid–fluid problems involving elastic–plastic solid behaviors. The solid, liquid, and gas behaviors are described by an Eulerian interface-capturing model derived from hyperelasticity theory. The deformations in each component of the solids are tracked using a single deviatoric strain tensor. The numerical algorithm employs a tenth-order compact finite difference scheme and a fourth-order Runge–Kutta time-stepping scheme. To prevent numerical oscillations near the material interface, a mechanical equilibrium assumption is introduced for the elastic–plastic problems, and a localized artificial diffusivity method satisfying this assumption is designed and applied in the numerical algorithm. Numerical tests in one and two dimensions are shown to demonstrate the accuracy and feasibility of the proposed approach. In particular, the accuracy and numerical resolution of the method are verified using problems with analytical solutions. Numerical tests of interface advection problems demonstrate that our method preserves the velocity, pressure, and elastic stress equilibria at the material interface and prevents overshoots in the rest of the domain. The two-dimensional Richtmyer–Meshkov instabilities between two elastic or two elastic–plastic solids are simulated to verify the suitability of the numerical method for solving problems involving large deformations. Impact of a 2D Taylor bar to a rigid wall is also simulated to test the robustness of the numerical method. Highlights: We construct a high order scheme simulating multi-material elastic–plastic solids. A mechanical equilibrium assumption is introduced to eliminate pressure oscillation. We prove that our numerical method satisfies the mechanical equilibrium assumption. Test problems show that our numerical method is pressure oscillation free. We simulate Richtmyer–Meshkov instability between elastic–plastic solids in 2D. We simulate Taylor rod impacting rigid wall in 2D.